Electronic Monitoring in Scotland - Graham, Hannah (2016)
This research report examines the current uses of electronic monitoring (EM) tagging technology in the Scottish criminal justice system. Findings and recommendations released in this report by Stirling criminologists Prof Gill McIvor and Dr Hannah Graham indicate support among criminal justice practitioners to make key changes to the use of electronic monitoring tagging in Scotland. Their study sought the views of criminal justice social workers, Scottish Prison Service staff, sheriffs, the Parole Board for Scotland, Police Scotland, G4S monitoring staff, Scottish Government policymakers, and a third sector organisation. The themes and findings presented here form one part of an EU-funded international comparative research project involving five jurisdictions: England and Wales, Scotland, Belgium, Germany and the Netherlands. Significantly, this is the first comparative study of its kind of electronic monitoring in Europe